FORMULASI DAN EVALUASI HAND SANITIZER SPRAY EKSTRAK BUAH BELIMBING WULUH (Averrhoa bilimbi L) - Ferdy Firmansyah (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
The tendency of society at this time to return to nature (Back to nature) is by using plants as treatment. The use of star fruit as the main ingredient in the manufacture of a hand sanitizer spray on the basis of star fruit has flavonoid compounds that have the potential as antibacterial. Hand sanitizer spray is made into 3 formulas with a concentration ratio of F1 (10%), F2 (12%), and F3 (15%). Each formula was subjected to physical tests in the form of organoleptic tests, pH tests, homogeneity tests and freeze and thaw stability tests for 6 storage cycles at 4Â°C and 40Â°C. The organoleptic results showed that the preparation did not change during four weeks of storage. On examination, the pH of the preparation decreased for F1 with a pH of 5.25 to 4.88; F2 with a pH of 5.14 becomes 4.77, and F3 with a pH of 4.87 becomes 4.60 but this value is still included in the specified range. The homogeneity of the preparations F1, F2, and F3 was only homogeneous in the first week and for the stability of the preparations F1, F2 and F3 were only stable in cycle 1 and cycle 2.